Studying the Effect of Zn2SnO4 Nanoparticles on Antibacterial Activity Using the Sol-Gel Method - Kawther, Kawther; Ziad T. Khodair; Firas Mahmoud Hadi (ASJ - Academic Science Journal, 2025)
In this study, zinc stannate Zn2SnO4 (ZTO) nanoparticles were prepared using the sol-gelmethod. X-ray diffraction technique was used to investigate the Zn2SnO4 nanoparticles, whichshowed that they have a polycrystalline structure and were of the cubic type. Field emissionscanning electron microscopy (FE-SEM) measurements showed that the grains werenanostructures with regular shapes, and their average atom dimensions were 162.01 nm.Transmission electron microscopy (TEM) showed the appearance of nanosheets and othersresembling nanoscale tilts. Zn2SnO4 nanoparticles showed biological activity againstpathogenic bacteria and showed a difference in the average diameter of inhibition for all typesof used bacteria, and the average diameter of inhibition ranged from 11 to 17 mm.